Predictors of knowledge, attitude and practice of noise induced hearing loss among workers in an automotive industry in Malaysia - Mohd Zulkefli, Nor Afiah; Rusli, Mohammad Farhan; abdul rahman, Anita (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2017)
Introduction: Automotive workers are exposed to high level of noise as part of their daily work routine. Determining the predictors of knowledge, attitude and practice of noise induced hearing loss (NIHL) among automotive is important because it may help prevent a serious irreversible disease known as noise induced hearing loss. Methods: A cross sectional study in an automotive plant in Shah Alam, Selangor was conducted from January 2015 to May 2015 among 550 workers with response rate of 83%. Respondents were workers from the operational divisions, selected based on simple random sampling using validated, published (1) and reliable self-administered questionnaire that focused on knowledge, attitude and practice towards NIHL. Results: Logistic Regression was used to determine predictors and the predictors for satisfactory knowledge on noise induced hearing loss were perceived noise exposure as harmful noise (AOR=0.54, 95%CI = 1.02 - 3.41), years in service for more than 10 years (AOR=2.79, 95%CI = 1.71 – 4.56) and had received training on safety (AOR=1.94, 95%CI = 1.12 – 3.36). For satisfactory attitude the predictors were perceived noise exposure as harmful noise (AOR=3.79, 95%CI = 2.36 – 6.10), years in service for more than 10 years (AOR=0.56, 95%CI = 0.34 – 0.83) and tertiary level of education (AOR=3.61, 95%CI = 1.67 - 7.81). As for satisfactory practice the predictors were more than 10 years in service (AOR=2.16, 95%CI = 1.24 – 3.75) and had received training on safety (AOR=1.94, 95%CI = 1.26 – 2.99). Conclusions: The results from this study may be used to set appropriate measures and identify workers who are at risk of developing noise induced hearing loss.